THE EFFECT OF PROBIOTICS ON VETERINARY AND SANITARY ASSESSMENT OF BROILER CHIKENS MEAT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This scientific article provides information about effect of the “Activil-3” probiotic on growth indicators, product quality, productivity, bloods hematological and morphological indicators of broiler chickens.